RETRACTED: The use of mathematical modeling and IT technologies to create a modern commodity management system - Kukartsev Anatoly; Kravtsov Kirill; Panfilov Ilia; Suprun Elena; Boyko Andrei (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 138, 00001 (2024), https://doi.org/10.1051/bioconf/202413800001